2012
DOI: 10.4187/respcare.01497
|View full text |Cite
|
Sign up to set email alerts
|

Dead Space Fraction Changes During PEEP Titration Following Lung Recruitment in Patients With ARDS

Abstract: A significant change of V(D)/V(T), compliance and arterial oxygenation could be induced by PEEP titration in subjects with ARDS. Optimal PEEP in these subjects was 12 cm H₂O, because at this pressure level the highest compliance in conjunction with the lowest V(D)/V(T) indicated a maximum amount of effectively expanded alveoli. Monitoring of V(D)/V(T) was useful for detecting lung collapse and for establishing open-lung PEEP after a recruitment maneuver.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 32 publications
2
47
0
3
Order By: Relevance
“…The appropriate level of PEEP should correspond to the lowest dead-space fraction (V D /V T ), as has been reported many years ago by Suter et al 66 and more recently by Fengnei et al 28 Because end-tidal P CO 2 (P ETCO 2 ) is determined, in part, by V D /V T , there has been interest in the use of capnography to assess best PEEP. In an experimental model of ARDS, Murray et al 67 reported that best PEEP was associated with the smallest difference between P aO 2 and P ETCO 2 .…”
Section: Gas Exchangementioning
confidence: 94%
See 2 more Smart Citations
“…The appropriate level of PEEP should correspond to the lowest dead-space fraction (V D /V T ), as has been reported many years ago by Suter et al 66 and more recently by Fengnei et al 28 Because end-tidal P CO 2 (P ETCO 2 ) is determined, in part, by V D /V T , there has been interest in the use of capnography to assess best PEEP. In an experimental model of ARDS, Murray et al 67 reported that best PEEP was associated with the smallest difference between P aO 2 and P ETCO 2 .…”
Section: Gas Exchangementioning
confidence: 94%
“…PEEP is then decreased in 2-cm H 2 O decrements, and the compliance is measured at each step to determine best compliance. Others have used arterial oxygenation [25][26][27] or dead space 28 rather than compliance to identify best PEEP during the decremental PEEP titration. After using either compliance or oxygenation to identify the pressure at which recruitment is not maintained, the recruitment maneuver is then repeated, after which PEEP is set 2 cm H 2 O greater than the level identified as best compliance.…”
Section: Types Of Recruitment Maneuversmentioning
confidence: 99%
See 1 more Smart Citation
“…This is not a new approach to determining an optimal level of PEEP. [7][8][9][10][11][12] However, a quick look at the available evidence may leave clinicians questioning the usefulness of this method. In the provided Table of decremental PEEP studies there are noticeable differences in titration methods, monitored values, methods for prior recruitment, as well as what the "optimal" level of PEEP should be post procedure.…”
Section: Decremental Peep Titrationmentioning
confidence: 99%
“…Volumetric capnography is considered the best tool to measure dead-space volumes (physiological, alveolar, and anatomic), allowing a functional analysis and providing clinical clues about the efficiency of gas exchange. 3 The V D increases when the alveolar-capillary interface is compromised (eg, COPD, atelectasis, and ARDS), [15][16][17] during decreased pulmonary blood flow (eg, pulmonary embolism), 18 or when alveoli are overdistended (eg, high PEEP). Physiological dead space (V D ) involves the sum of anatomic V D , consisting of the portion of the airways that conducts gas without gas exchange, and alveolar V D , which consists of alveoli that are ventilated but not well perfused (V /Q mismatch).…”
mentioning
confidence: 99%